2016
DOI: 10.1002/ejoc.201600436
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of α‐Propargylglycinates Using the Borono‐Mannich Reaction with Pinacol Allenylboronate and Potassium Allenyltrifluoroborate

Abstract: The three component borono‐Mannich reactions of ethyl glyoxylate, primary or secondary amines and pinacol allenylboronate or potassium allenyltrifluoroborate are highly regioselective and give α‐propargylglycinates. The (S)‐N‐tert‐butylsulfinyl imine of ethyl glyoxylate underwent an indium chloride catalyzed addition reaction with allenyl potassium trifluoroborate in a highly regioselective and diastereoselective manner to give ethyl (S)‐α‐propargylglycinate after N‐deprotection in 97 % ee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Subsequently, an In-catalyzed variant of this reaction was reported. 8 Recently, Pyne and co-workers 9 demonstrated that N-tert-butylsulfinyl imines undergo In-catalyzed couplings with allenylboron species (Fig. 1b).…”
mentioning
confidence: 98%
“…Subsequently, an In-catalyzed variant of this reaction was reported. 8 Recently, Pyne and co-workers 9 demonstrated that N-tert-butylsulfinyl imines undergo In-catalyzed couplings with allenylboron species (Fig. 1b).…”
mentioning
confidence: 98%
“…The regioselectivity was generally excellent except for the reaction with primary amines. Pyne's group resolved this problem (Scheme 18c) [65] by introducing ethyl glycinate as an electrophile, which can not form a boronate intermediate through B−O coordination of the carboxylate group. However, this borono‐Mannich reaction only worked with the primary amine as a substrate.…”
Section: Reactivity Of Allenylboronmentioning
confidence: 99%
“…Reactive intermediates related to 44 and 50 (involving boron coordination to the CO 2 of the glyoxylic acid) may be also be involved. In a shorter study the Pyne group 35 found that the reaction of glyoxylic acid (monohydrate), pinacol allenylboronate 3, and dibenzylamine gave the corresponding α-allenylglycine of 54 (R 1 = R 2 = Bn) while the reaction using diphenylmethylamine, rather than dibenzylamine, gave a 27:73 mixture of propargyl and allenyl products, respectively.…”
Section: Short Review Syn Thesismentioning
confidence: 99%
“…The Pyne group 35 demonstrated that the borono-Mannich reactions of ethyl glyoxylate, primary or secondary amines, and pinacol allenylboronate 3 or potassium allenyltrifluoroborate (10) were highly regioselective and gave ethyl α-propargylglycinates 56 (Scheme 36). These results are different to those found using glyoxylic acid and allenylboronic acid 8, supporting the mechanisms shown in Scheme 37.…”
Section: Short Review Syn Thesismentioning
confidence: 99%
See 1 more Smart Citation